Papel dos receptores GABA-benzodiazepínicos da matéria cinzenta periaquedutal na modulação da ansiedade em camundongos ingênuos e reexpostos ao labirinto em cruz elevado - Reis, Luciana Maria dos (2006)
It is well known that the previous experience to the elevated plus-maze (EPM) increases the avoidance of rodents to the open arms and impairs the anxiolytic-like effect of benzodiazepines in a subsequent exposure to the EPM, a phenomenon known as "one trial tolerance" (OTT). This study investigated the effects of intra-periaqueductal gray matter (PAG) infusions of midazolam (MDZ) in EPM-naïve and EPM-experienced mice. The antiaversive effects of MDZ were also evaluated after prior injection of flumazenil, a benzodiazepine receptor antagonist, into to same midbrain site. Test videotapes were scored for conventional measures of anxiety (% open arm entries and % open arm time) and locomotor activity (frequency of closed arm entries), as well as a range of ethological measures related to risk assessment (e.g. stretch attend postures; head dips, etc). In EPMnaïve mice, intra-PAG infusions of MDZ increased % open arm entries (2.26 nmol) and % open arm time (2.26 and 30 nmol). These effects were observed in the absence of significant changes in locomotor activity, indicating a selective anxiolytic-like effect of MDZ. The antiaversive effects of MDZ were completely blocked by prior injection of flumazenil (16 nmol) into the same midbrain site, and did not alter any behavioral measures per se. In EPMexperienced mice, intra-PAG infusion of MDZ did not modify any behavioral measures. Taken together, present results demonstrates that GABA-benzodiazepine receptor complex located within the PAG plays a role on anxiety modulation in EPM-naïve mice as well as indicates its involvement in the OTT phenomenon.